Childhood Hypertrophic Cardiomyopathy: A Disease of the Cardiac Sarcomere - Norrish, Gabrielle; Field, Ella; Kaski, Juan P. (Frontiers in Pediatrics, 2021)
Hypertrophic cardiomyopathy is the second most common cause of cardiomyopathy presenting during childhood and whilst its underlying aetiology is variable, the majority of disease is caused by sarcomeric protein gene variants. Sarcomeric disease can present at any age with highly variable disease phenotype, progression and outcomes. The majority have good childhood-outcomes with reported 5-year survival rates above 80%. However, childhood onset disease is associated with considerable life-long morbidity and mortality, including a higher SCD rate during childhood than seen in adults. Management is currently focused on relieving symptoms and preventing disease-related complications, but the possibility of future disease-modifying therapies offers an exciting opportunity to modulate disease expression and outcomes in these young patients.